Incorporating biodiversity into the sustainability assessment of livestock systems using comprehensive life cycle assessment: A mini-review - Sooriya Patabendige, Malith S.; Uddin, Md Elias (Frontiers in Sustainable Food Systems, 2025)
Livestock significantly contribute to biodiversity loss, primarily due to changes in land use, overexploitation of natural resources, pollution, and climate change. Intensive farming systems that depend heavily on resource inputs accelerate the decline of species and exert immense pressure on biodiversity, ultimately making the industry unsustainable. Identifying hotspots and quantifying their impacts along the value chain of animal products help producers and policymakers make informed decisions and provide insights to guide consumers toward more environmentally conscious purchasing. Life cycle assessment (LCA) provides a holistic approach to assessing the environmental footprint (EF) throughout the life cycle of a product or service. However, ecosystem services, such as biodiversity, are often not integrated into LCA, particularly in the context of livestock systems. Existing studies and methodologies frequently fail to illustrate the impacts of biodiversity under various management practices. In addition, the majority of these studies focus on a single midpoint impact category related to land use change, which is based on the species–area relationship (SAR) and metrics at the species level. However, due to the dynamic and complex nature of biodiversity, relying a single midpoint impact or metric alone is insufficient to capture the full spectrum, and it does not provide a comprehensive understanding of the impacts. In addition, the lack of consensus on characterization factors (CFs), limitations in data availability (i.e., conservation status of taxa at local and regional levels), and challenges in assigning weights to taxa and ecological functions based on their significance are key limitations that need to be addressed in future LCA studies.